MENGGALAKKAN PROGRAM TRANSMIGRASI MELALUI PENINGKATAN PEMBANGUNAN DAERAH - I Gde, Nitiyasa; I Ketut, Sudibia (PIRAMIDA; Vol 9, No. 1 Juli 2013, 2013)
During the Dutch colonial government, migration activity which was known as colonization was done since 1905. This program had been continued up towards the World War II, then also during independence era which is then called transmigration. Although transmigration has been carried out for a long time, its objective to relocate population from Java to the other part of Indonesia is still relatively low. Java Island which covers an area of 7 percent of Indonesia’s land is populated by about 57 percent of total Indonesia’s population (Population Census 2010). In the past, transmigration policy tended to be demographic centric, which migrated people from densely to sparsely populated areas. To eliminate demographic centric image, it is necessary to reorient the transmigration policy to be more regional development based. There are four targets of regional development: (a) to develop new villages by building integrated transmigration settlement in one development area; (b) to develop a hinterland of existing growth centers; (c) to improve less developed villages by increasing population and developing the infrastructures; and (d) to develop transmigration society and local people through improving society self-supporting skills. During the decentralization era, there are at least three policy steps that should be done, including (1) to control inflow of migrants in terms of number of social economic characters and potential conflicts with local people; (2) to group integrated migrants from various ethnic and prepare skilled migrants in each group and location; and (3) to plan infrastructure development, such as roads, bridges, irrigation, clinic, sport centers, and other facilities which are not seem to be exclusive for certain location.
Keywords: transmigration, reorientation; decentralization; regional development